The Charter of Whites: Systemic Racism and Critical Race Equality in Canada - Sealy-Harrington, Joshua (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2023)
This article outlines the concept of “critical race equality” in Canadian constitutional law and critiques the Supreme Court of Canada’s jurisprudential silence on systemic racism under section 15 of the Charter. First, the article discusses the theory of critical race equality. It describes six principles that animate a critical race perspective, which understands equality as ambitious, contextual, ideological, comparative, systemic, and positive. Second, the article discusses the practice of critical race equality. It traces a genealogy from the Supreme Court’s first equality decision (Andrews) to its latest (Fraser), both of which reflect the principles of critical race equality. This genealogy demonstrates that critical race equality has been consistently affirmed by the Supreme Court, yet has never been applied by the Court to ubiquitous systemic inequality confronting Black and Indigenous communities in Canada. This article concludes that systemic racial justice advocacy under section 15 of the Charter is doctrinally viable. Consequently, it calls upon a coalition of scholars, lawyers, and organizers to recognize that viability as one of many tools for challenging unconstitutional state neglect and advancing systemic racial justice.